2021
DOI: 10.1155/2021/6649660
|View full text |Cite
|
Sign up to set email alerts
|

Genes That Predict Poor Prognosis in Breast Cancer via Bioinformatical Analysis

Abstract: Background. Breast cancer is one of the most commonly diagnosed cancers all over the world, and it is now the leading cause of cancer death among females. The aim of this study was to find DEGs (differentially expressed genes) which can predict poor prognosis in breast cancer and be effective targets for breast cancer patients via bioinformatical analysis. Methods. GSE86374, GSE5364, and GSE70947 were chosen from the GEO database. DEGs between breast cancer tissues and normal breast tissues were picked out by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“… 33 Some reports have indicated that HMMR is a gene for poor prognosis of BC, and its dysregulation is closely associated with tumor cell phenotype and microenvironment. 34 , 35 In this work, raised HMMR in BC samples and cells was seen, consistent with previous reports. Of note, functional analysis discovered that the overexpression of HMMR might partially alleviate the malignant phenotype of BC cells and the inhibition of glutamine metabolism induced by circ_0005273 deletion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 33 Some reports have indicated that HMMR is a gene for poor prognosis of BC, and its dysregulation is closely associated with tumor cell phenotype and microenvironment. 34 , 35 In this work, raised HMMR in BC samples and cells was seen, consistent with previous reports. Of note, functional analysis discovered that the overexpression of HMMR might partially alleviate the malignant phenotype of BC cells and the inhibition of glutamine metabolism induced by circ_0005273 deletion.…”
Section: Discussionsupporting
confidence: 92%
“…Existing evidence has revealed that HMMR is often freakishly expressed in human tumors and its overexpression might accelerate the formation and progression of different cancers, such as lung adenocarcinoma 32 and colon cancer 33 . Some reports have indicated that HMMR is a gene for poor prognosis of BC, and its dysregulation is closely associated with tumor cell phenotype and microenvironment 34,35 . In this work, raised HMMR in BC samples and cells was seen, consistent with previous reports.…”
Section: Discussionsupporting
confidence: 91%
“…These show that elevated RHAMM expression is characteristic of most cancers and prognostic of a poor outcome in many. For example, elevated RHAMM expression is an indicator of poor prognosis in breast cancer [ 119 , 120 , 121 ], multiple myeloma [ 122 ], oral squamous cell carcinoma [ 123 ], ovarian cancer [ 124 ], lung cancer [ 125 ], prostate cancer [ 126 ], colon cancer [ 127 ], and gastric cancer [ 128 ]. However, histology analyses of these human tumors reveal that RHAMM expression is heterogeneous, and high RHAMM expression is often limited to a small subset of cancer cells [ 119 ].…”
Section: Rhamm Multi-functions In Cancermentioning
confidence: 99%
“…Many genes exhibit differences in expression levels between normal and cancer tissues. In addition, certain genes demonstrate significant changes in expression levels in cancer tissues with a poor prognosis 9 , 10 . It is possible that subsequent treatment could be changed or modified depending on the gene expression pattern in the cancer.…”
Section: Introductionmentioning
confidence: 99%